Examination of the crime scene during the investigation of official criminal offenses committed by law enforcement officers - Chepurna, T. V. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The article is devoted to the study of the specifics of conducting a crime scene examination as a key investigative (detective) action in the process of investigating official criminal offenses committed by law enforcement officers. The procedural, organizational, and tactical aspects of the examination are analyzed, taking into account the specifics of offenses such as abuse of power or official position, exceeding authority, official forgery, and acceptance of an unlawful benefit by an official. It is established that the purpose of the crime scene examination is to detect and document traces of a criminal offense, documents, digital storage devices, as well as signs of external interference with the scene. Special attention is given to the main tasks of the examination: detailed documentation of the environment, detection of attempts to conceal or falsify evidence, verification of the consistency between factual data and official reports, and seizure of digital evidence. The article examines challenges associated with restricted access to official premises, the phenomenon of corporate solidarity among colleagues, and the professional awareness of offenders, which complicate the investigation. Recommendations are proposed to improve the tactics of examination, including ensuring the element of surprise, involving cyberforensics experts, utilizing modern forensic tools. The importance of an operational and procedurally sound approach is emphasized to preserve the authenticity of the evidentiary base. Effective crime scene examination creates the basis for constructing well-founded investigative versions, identifying the circle of involved individuals, and ensuring completeness and objectivity in the criminal process. The article is based on the analysis of scientific literature, case law, and materials from criminal proceedings, which allowed for the systematization of approaches to organizing and conducting crime scene examinations under conditions of resistance to the investigation. The study highlights the need for a comprehensive approach to enhance the effectiveness of this investigative action in the specific context of investigating official offenses committed by law enforcement personnel.